PENGARUH GENDER DAN KEMAMPUAN AKADEMIS TERHADAP MINAT PERUSAHAAN DALAM PEREKRUTAN AKUNTAN - Ghifran Al Afghani; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2022)
This study aims to determine the effect of gender and ability on the company's interest in the processing of recruiting accountants. It is a quantitative study using primary data obtained from questionnaires and measured using a Likert Scale. The population in this study is the HRD of companies operating in the City / Regency of Pasuruan. Sampling with the help of Bank employees who receive cash deposits from customers / companies every day with the result that there are as many as 30 respondents. The method of determining the sample is purposive sampling. This data analysis technique uses SPSS 18.0 for windows. The results of the research show: 1) Gender and Academic Ability variables have a simultaneous effect on the Company's interest in Accountant Recruitment, 2) According to the T-Test, Gender Variable has